YIG gyromagnetic ferrite material capable of effectively reducing ferromagnetic resonance line width and preparation method thereof

By introducing specific ions into the YIG rotary magnet ferrite material and using multi-ion to replace the activated YIG ferrite lattice, the problem of difficulty in reducing the ferromagnetic resonance line width of the YIG rotary magnet ferrite material in the prior art is solved, and the performance improvement of the material is achieved, including reducing the ferromagnetic resonance line width, increasing the saturation magnetization and density, and reducing coercive force.

CN119569435APending Publication Date: 2025-03-07CHINA UNIV OF MINING & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411644475.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the ferromagnetic resonance line width in YIG rotary magnet ferrite materials, affecting its electromagnetic performance.

Method used

By introducing Ca2+, Ce3+, Mn2+ and Zr2+ ions into the YIG rotary magnet ferrite material, replacing the positions of Y3+ and Fe3+ respectively, forming a chemical structure of Ca0.3CexY2.7-xMn0.05Zr0.45Fe4.5O12, multi-ion substitution activates the YIG ferrite lattice, and optimizing the microstructure of the material through a specific sintering process.

Benefits of technology

The ferromagnetic resonance line width of YIG rotary magnet ferrite material is significantly reduced, from 867.4Oe to 310.9Oe, which improves the saturation magnetization and density of the material, reduces coercivity, and improves microwave characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569435A_ABST
    Figure CN119569435A_ABST
Patent Text Reader

Abstract

The invention discloses a YIG gyromagnetic ferrite material capable of effectively reducing ferromagnetic resonance line width and a preparation method thereof, the chemical formula of the YIG gyromagnetic ferrite material is Ca < 0.3 > CexY < 2.7-x > Mn < 0.05 > Zr < 0.45 > Fe < 4.5 > O12, x is greater than or equal to 0 and less than or equal to 0.5, the YIG gyromagnetic ferrite material has a complete garnet structure, Ca < 2 + > and Ce < 3 + > replace dodecahedral Y < 3 + > ions of a YIG ferrite lattice structure, and Mn < 2 + > and Zr < 2 + > respectively replace octahedral Fe < 3 + > of the YIG ferrite lattice structure; meanwhile, Bi2O3 is introduced as a sintering aid to promote the YIG ferrite to be fully sintered at 1280 DEG C, so that the microwave characteristics of the material are improved, the saturation magnetization is higher, the coercive force is lower, more importantly, the ferromagnetic resonance line width can be greatly narrowed, and the material becomes a base material of a microwave ferrite device with high integration level, small size and excellent electromagnetic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic ceramics, and in particular relates to a YIG gyromagnetic ferrite material capable of effectively reducing the ferromagnetic resonance line width and a preparation method thereof. Background Art

[0002] With the advancement of modern microwave communication technology, microwave devices continue to develop in the direction of smaller size, lighter weight, lower cost and higher sensitivity. For example, microwave devices such as circulators, phase shifters, isolators, tuned oscillators and coordinated filters have been well applied in electronic equipment for radar, communication, electronic countermeasures and artificial intelligence. In order to meet the needs brought about by technological development, the basic materials of microwave devices need to have greater improvements in electromagnetic performance. YIG ferrite is a typical gyromagnetic material. As the basic material of microwave devices, it has many excellent properties, such as high resistivity, high saturation magnetization, high dielectric constant, low dielectric loss and narrow ferromagnetic resonance linewidth. Since the size of the ferromagnetic resonance linewidth directly reflects the size of the damping coefficient, the narrow ferromagnetic resonance linewidth as an important characteristic of YIG ferrite will directly affect the performance of YIG ferrite. How to effectively reduce the ferromagnetic resonance linewidth in YIG ferrite has become a hot issue that needs to be solved.

[0003] At present, the realization of reducing the ferromagnetic resonance linewidth of YIG gyromagnetic ferrite mainly focuses on using LTCC technology, different preparation processes and ion substitution methods. A Chinese patent with application number 202110324952.9 and invention name "A low-temperature sintered YIG gyromagnetic ferrite material and its preparation method" discloses a preparation process for producing fine-grained yttrium iron garnet by low-temperature sintering using LTCC technology. The invention places the pressed powder in a sintering furnace and heats it to 400°C at a rate of 2°C / min under an oxygen atmosphere, keeps it warm for 1 to 2 hours, then heats it to 500°C at the same rate, keeps it warm for 1 to 2 hours, then heats it to 900-960°C at the same rate, keeps it warm for 2 to 4 hours, then cools it to 600°C at a rate of 2°C / min and naturally cools it to room temperature with the furnace to obtain the low-temperature sintered YIG gyromagnetic ferrite material; however, the YIG gyromagnetic ferrite obtained in this process has a very limited reduction in the ferromagnetic resonance linewidth, and fails to effectively reduce the ferromagnetic resonance linewidth. In the paper “High dielectric constant and magnetic properties of Bi-In Co-substituted YIG ferrites”, Lu Bing et al. systematically studied the phase structure, micromorphology, dielectric properties and magnetic properties of Ca-Sn-Zr ion-doped Bi:YIG ferrite materials; the results showed that Ca-Sn-Zr ions entered the garnet crystal, no second phase was generated in the crystal, and the lattice constant increased with the increase of doping amount. In terms of magnetic properties, an appropriate amount of Ca-Sn-Zr ions can increase the saturation magnetization intensity of the material, reduce the coercive force and ferromagnetic resonance linewidth. However, the effect of a small amount of doping is limited, and increasing the doping concentration will increase the ferromagnetic resonance linewidth. Xuening Han et al. studied the YIG ferrite material Y co-substituted by Bi-In synthesized by the traditional solid phase method in the paper “High dielectric constant and magnetic properties of Bi-In Co-substituted YIG ferrites”. 3- x Bi x Fe 4.55 In 0.45 O 12 (x=0.0-1.0, step size 0.2), it is found that although dense YIG ceramics have good electromagnetic properties, increasing the doping concentration will lead to an increase in the ferromagnetic resonance line width. Based on the above analysis, in order to improve the electromagnetic properties of YIG gyromagnetic ferrite materials and reduce the ferromagnetic resonance line width, it is necessary to seek new ion doping and processes to meet the needs of improving electromagnetic properties. Summary of the invention

[0004] The object of the present invention is to provide a YIG spinel ferrite material capable of effectively reducing the ferromagnetic resonance linewidth and its preparation method, which can effectively reduce the ferromagnetic resonance linewidth, improve the saturation magnetization and density of the YIG spinel ferrite, and reduce the coercive force.

[0005] To achieve the above object of the invention, the present invention provides a YIG spinel ferrite material capable of effectively reducing the ferromagnetic resonance linewidth. The chemical formula of the YIG spinel ferrite material is Ca 0.3 Ce x Y 2.7-x Mn 0.05 Zr 0.45 Fe 4.5 O 12 , where 0 ≤ x ≤ 0.5.

[0006] Furthermore, the YIG spinel ferrite material has a complete garnet structure. Ca 2+ and Ce 3+ are used to replace Y 3+ in the dodecahedral position of the YIG spinel ferrite lattice structure, and Mn 2+ and Zr 2+ are respectively used to replace Fe 3+ in the octahedral position of the YIG spinel ferrite lattice structure.

[0007] To achieve the above object of the invention, the present invention also provides a preparation method of the above YIG spinel ferrite material capable of effectively reducing the ferromagnetic resonance linewidth, including the following steps:

[0008] S1. Weighing and batching: Using Y2O3, Fe2O3, CeO2, MnO, ZrO2, CaO as raw materials, weighing the raw materials according to the chemical formula Ca 0.3 Ce x Y 2.7- x Mn 0.05 Zr 0.45 Fe 4.5 O 12 , where 0 < x ≤ 0.5; or using Y2O3, Fe2O3, MnO, ZrO2, CaO as raw materials, weighing the raw materials according to the chemical formula Ca 0.3 Y 2.7 Mn 0.05 Zr 0.45 Fe 4.5 O 12 ;

[0009] S2. Primary ball milling: Using the wet milling method to perform primary ball milling on the raw materials, drying, sieving, and then pre-burning at 1200 °C in an oxygen atmosphere for 2 - 3 h, and cooling to room temperature with the furnace to obtain the YIG spinel ferrite pre-burned material;

[0010] S3, secondary ball milling: sieve the YIG ferrite pre-sintered material powder obtained in step S2, add 1-2% Bi2O3 as a sintering aid to the YIG ferrite pre-sintered material, perform secondary ball milling on the sieved YIG ferrite pre-sintered material by wet milling, and dry the secondary ball milled material;

[0011] S4, molding: after the secondary ball mill material is screened, 8-10 wt% of the total weight of the raw material is added with a polyvinyl alcohol binder for granulation, and then pressed into a ring sample under a pressure of 10-12 MPa;

[0012] S5, sintering: placing the sample obtained in step S3 into a sintering furnace, heating it to 500°C at a rate of 2°C / min, keeping it warm for 1-2h, then heating it to 1280°C at the same rate, keeping it warm for 3.5h, then cooling it to 100°C at a rate of 2°C / min, and then naturally cooling it to room temperature in the furnace to obtain the YIG gyromagnetic ferrite material that can effectively reduce the ferromagnetic resonance linewidth.

[0013] Furthermore, in step S2, the specific process of the wet grinding method is: using deionized water as the ball milling medium, placing the raw materials into a ball milling tank, adding deionized water in a ratio of 1:1.2 of the mass ratio of raw materials to deionized water, and using a planetary ball mill to perform ball milling for 4 to 8 hours at a ball milling speed of 240 to 260 rpm.

[0014] Furthermore, in step S3, the specific process of the wet grinding method is: using deionized water as the ball milling medium, placing the pre-burned material into a ball milling tank, adding deionized water in a ratio of 1:1.2 of the mass ratio of the pre-burned material to deionized water, and using a planetary ball mill to perform ball milling for 4 to 8 hours at a ball milling speed of 240 to 260 rpm.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] (1) In the YIG gyromagnetic ferrite material provided by the present invention, Ca 2+ Ions and Ce 3+ Substituting Y in the dodecahedral position of the YIG ferrite lattice structure 3+ Ion, using Mn 2+ and Zr 2+ The ions replace the Fe in the octahedral site of the YIG ferrite lattice structure. 3+ Ions, achieving multi-ion substitution activation of the YIG ferrite lattice while also improving the microwave properties of the material;

[0017] (2) The YIG gyromagnetic ferrite material prepared by the present invention has a narrow ferromagnetic resonance line width. As the Ce ion doping concentration increases, the ferromagnetic resonance line width decreases from 867.4 Oe to 310.9 Oe, showing an overall downward trend with a significant decrease, which reflects the improvement of YIG performance by adding Ce ions;

[0018] (3) The YIG gyromagnetic ferrite prepared by the present invention has a narrow ferromagnetic resonance line width, a high saturation magnetization (>20emu / g) and a low coercive force, and provides a basic material for the manufacture of microwave ferrite devices with high integration requirements and small volume requirements;

[0019] (4) The YIG gyromagnetic ferrite prepared by the present invention not only has good gyromagnetic properties, but also has good compactness. The density of YIG ferrite is 4.0g / cm 3 above. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The XRD patterns of the samples obtained in Examples 1-4 of the present invention are shown in FIG.

[0021] Figure 2 The SEM images of the samples obtained in Example 1 (a), Example 2 (b), Example 3 (c), and Example 4 (d) respectively;

[0022] Figure 3 The ferromagnetic resonance line width FMR graphs of the samples obtained in Example 1 (a), Example 2 (b), Example 3 (c), and Example 4 (d) respectively;

[0023] Figure 4 VSM diagrams of the hysteresis loops of the samples obtained in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with specific embodiments.

[0025] Example 1

[0026] This embodiment provides a YIG gyromagnetic ferrite material that can effectively reduce the ferromagnetic resonance line width. 2+ and Ce 3+ Substituting Y in the dodecahedral position of the YIG ferrite lattice structure 3+ On the basis of 2+ and Zr 2+ Substituting Fe in the octahedral position of YIG ferrite 3+ , we can obtain YIG gyromagnetic ferrite which can effectively reduce the ferromagnetic resonance line width: Ca 0.3 Ce x Y 2.7-x Mn 0.05 Zr 0.45 Fe 4.5 O 12 , x=0, while reducing the ferromagnetic resonance linewidth of YIG gyromagnetic ferrite, the excellent performance of higher saturation magnetization intensity, higher density, lower coercive force and lower microwave loss is obtained.

[0027] In this embodiment, the preparation method of the above YIG gyromagnetic ferrite material comprises the following specific steps:

[0028] S1. Weighing ingredients: Y2O3, Fe2O3, MgO, ZrO2, CaO are used as raw materials, according to the chemical formula Ca 0.3 Y 2.7 Mn 0.05 Zr 0.45 Fe 4.5 O 12 Weighing raw materials;

[0029] S2, primary ball milling: after the raw materials are placed in a ball milling jar, deionized water is added as a ball milling medium in a mass ratio of 1:1.2 between the raw materials and deionized water, and then a planetary ball mill is used for primary ball milling for 4 hours at a ball milling speed of 240 rpm to mix the powders evenly, and then the powders are dried and sieved and pre-calcined at 1200°C in an oxygen atmosphere for 2 hours to obtain a YIG gyromagnetic ferrite pre-calcined material;

[0030] S3, secondary ball milling: after the YIG ferrite pre-sintered powder obtained in step S2 is sieved through an 80-mesh sieve, 1% Bi2O3 of the YIG ferrite pre-sintered powder is added to the pre-sintered powder as a sintering aid, deionized water is added in a ratio of 1:1.2 between the pre-sintered powder and deionized water, and secondary ball milling is performed for 4 hours using a planetary ball mill at a ball milling speed of 240 rpm. After the ball milling is completed, the secondary ball milled powder is taken out and dried;

[0031] S4, molding: After the secondary ball mill material is sieved, a polyvinyl alcohol (PVA) binder equivalent to 10 wt% of the total mass of the raw material is added for granulation, and then pressed into a ring sample at a pressure of 10 MPa using a hydraulic press;

[0032] S5. Sintering: Place the sample in a sintering furnace, heat it to 500°C at a rate of 2°C / min, keep it warm for 2 hours to remove water vapor and glue, then heat it to 1280°C at the same rate, keep it warm for 3.5 hours to complete the sintering, then cool it to 100°C at a rate of 2°C / min and naturally cool it to room temperature in the furnace to obtain the YIG gyromagnetic ferrite material.

[0033] The performance parameters of the YIG gyromagnetic ferrite material prepared in this embodiment are: saturation magnetization 4πMs is 27.101emu / g, density is 4.362g / cm 3 , the ferromagnetic resonance line width ΔH is 867.391Oe, and the coercive force Hc is 14.801Oe.

[0034] Example 2

[0035] Compared with Example 1, the difference between this embodiment and Example 1 is as follows: S1, weighing ingredients: Y2O3, Fe2O3, CeO2, MgO, ZrO2, CaO are used as raw materials, according to the chemical formula Ca 0.3 Ce x Y 2.7-x Mn 0.05 Zr 0.45 Fe 4.5 O 12 (x=0.1) weigh the raw materials; the remaining steps are consistent with Example 1.

[0036] The performance parameters of the YIG gyromagnetic ferrite material prepared in this embodiment are: saturation magnetization 4πMs is 27.893emu / g, density is 4.378g / cm 3 , the ferromagnetic resonance line width ΔH is 863.198Oe, and the coercive force Hc is 18.808Oe.

[0037] Example 3

[0038] Compared with Example 1, the difference between this embodiment and Example 1 is as follows: S1, weighing ingredients: Y2O3, Fe2O3, CeO2, MgO, ZrO2, CaO are used as raw materials, according to the chemical formula Ca 0.3 Ce x Y 2.7-x Mn 0.05 Zr 0.45 Fe 4.5 O 12 (x=0.3) Weigh the raw materials; the remaining steps are consistent with Example 1.

[0039] The performance parameters of the YIG gyromagnetic ferrite material prepared in this embodiment are: saturation magnetization 4πMs is 28.296emu / g, density is 4.551g / cm3, ferromagnetic resonance line width ΔH is 541.623Oe, and coercive force Hc is 15.605Oe.

[0040] Example 4

[0041] Compared with Example 1, the difference between this embodiment and Example 1 is as follows: S1, weighing ingredients: Y2O3, Fe2O3, CeO2, MgO, ZrO2, CaO are used as raw materials, according to the chemical formula Ca 0.3 Cex Y 2.7-x Mn 0.05 Zr 0.45 Fe 4.5 O 12 (x=0.5) weigh the raw materials; the remaining steps are consistent with Example 1.

[0042] The performance parameters of the YIG gyromagnetic ferrite material prepared in this embodiment are: saturation magnetization 4πMs is 24.185emu / g, density is 4.677g / cm3, ferromagnetic resonance line width ΔH is 310.992Oe, and coercive force Hc is 15.347Oe.

[0043] Depend on Figure 1 It can be seen that the YIG ferrite obtained by the present invention presents a complete garnet phase, almost no impurity phase appears, and the ion substitution is successful. Figure 2 It can be seen that the YIG ferrite prepared by the present invention has fewer pores between grains, and the multi-ion substitution reduces the porosity of the sample and improves the compactness of the YIG gyromagnetic ferrite sample. Figure 3 It can be seen that multi-ion doping can effectively reduce the ferromagnetic resonance line width of YIG gyromagnetic ferrite samples at a suitable sintering temperature. Figure 4 It can be seen that the YIG gyromagnetic ferrite obtained by the present invention has a higher saturation magnetization intensity and a lower coercive force.

Claims

1. A YIG gyromagnetic ferrite material that can effectively reduce the ferromagnetic resonance line width, characterized in that: The chemical formula of the YIG gyromagnetic ferrite material is Ca 0.3 Ce x Y 2.7-x Mn 0.05 Zr 0.45 Fe 4.5 O 12 , where 0≤x≤0.

5.

2. The YIG gyromagnetic ferrite material capable of effectively reducing the ferromagnetic resonance line width according to claim 1, characterized in that: The YIG gyromagnetic ferrite material has a complete garnet structure and uses Ca 2+ and Ce 3+ Substituting Y in the dodecahedral position of the YIG gyromagnetic ferrite lattice structure 3+ , using Mn 2+ and Zr 2+ Substituting Fe in the octahedral position of the YIG gyromagnetic ferrite lattice structure 3+ .

3. A method for preparing a YIG gyromagnetic ferrite material capable of effectively reducing the ferromagnetic resonance line width as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1. Weigh the ingredients: Using Y2O3, Fe2O3, CeO2, MnO, ZrO2, and CaO as raw materials, according to the chemical formula Ca 0.3 Ce x Y 2.7- x Mn 0.05 Zr 0.45 Fe 4.5 O 12 weigh the raw materials, where 0 < x ≤ 0.5; or using Y2O3, Fe2O3, MnO, ZrO2, and CaO as raw materials, according to the chemical formula Ca 0.3 Y 2.7 Mn 0.05 Zr 0.45 Fe 4.5 O 12 weigh the raw materials; S2. First ball milling: The raw material is ball milled once by wet milling, dried, sieved, and then pre-fired at 1200°C in an oxygen atmosphere for 2-3 hours, and then cooled to room temperature with the furnace to obtain a YIG ferrite pre-fired material; S3, secondary ball milling: sieve the YIG ferrite pre-sintered material powder obtained in step S2, add 1-2% Bi2O3 as a sintering aid to the YIG ferrite pre-sintered material, perform secondary ball milling on the sieved YIG ferrite pre-sintered material by wet milling, and dry the secondary ball milled material; S4, molding: after the secondary ball mill material is screened, 8-10 wt% of the total weight of the raw material is added with a polyvinyl alcohol binder for granulation, and then pressed into a ring sample under a pressure of 10-12 MPa; S5, sintering: placing the sample obtained in step S3 into a sintering furnace, heating it to 500°C at a rate of 2°C / min, keeping it warm for 1-2h, then heating it to 1280°C at the same rate, keeping it warm for 3.5h, then cooling it to 100°C at a rate of 2°C / min, and then naturally cooling it to room temperature in the furnace to obtain the YIG gyromagnetic ferrite material that can effectively reduce the ferromagnetic resonance linewidth.

4. The method for preparing a YIG gyromagnetic ferrite material capable of effectively reducing the ferromagnetic resonance line width according to claim 3, characterized in that: In step S2, the specific process of the wet grinding method is: using deionized water as the ball grinding medium, placing the raw materials into a ball grinding tank, adding deionized water in a ratio of 1:1.2 of the raw materials to deionized water, and using a planetary ball mill to perform ball grinding for 4 to 8 hours at a ball milling speed of 240 to 260 rpm.

5. The method for preparing a YIG gyromagnetic ferrite material capable of effectively reducing the ferromagnetic resonance line width according to claim 3, characterized in that: In step S3, the specific process of the wet grinding method is: using deionized water as the ball milling medium, placing the pre-burned material into a ball milling jar, adding deionized water at a mass ratio of 1:1.2 between the pre-burned material and deionized water, and using a planetary ball mill to perform ball milling for 4 to 8 hours at a ball milling speed of 240 to 260 rpm.

Citation Information

Patent Citations

  • Microwave ferrite material with small line width and high curie temperature and preparation method thereof

    CN103833347A

  • Garnet ferrite with high temperature stability and preparation method thereof

    CN109867518A

  • Low-loss YIG material and preparation method thereof

    CN114644516A

  • Magnetic materials for microwave and production methodthereof

    KR1020030070389A